Molecular identification of the most frequent pathotypes of Escherichia coli in calves with diarrhoea in the Cajamarca region of Peru - Cabrera González, Marco (2024)
Background: Colibacillosis caused by Escherichia coli causes significant economic losses in the livestock sector worldwide and is one of the calves’ leading causes of diarrea Aim: This study aimed to identify the most frequent E. coli molecularly pathotypes in calves with diarrhea in six provinces of the Cajamarca region in the northern highlands of Peru. Methods: Twenty-eight herds of dairy cattle under a semi-intensive rearing system were evaluated; 95 samples were isolated from calves with diarrhea up to the first month of life, 62 males and 33 females, during the rainy season. Results: The presence of virulence genes of E. coli strains was more prevalent in males; the astA (89.47%), st (83.15%), and f5 (57.89%) genes were more expressed, and the lt (17.89%) and stx2 (1.05%) genes were less expressed. The eae gene (21.05%) was more present in females. Conclusion: When E. coli strains express virulence genes astA, st, and f5 and their atypical double, triple, and quadruple combination between different observed pathotypes, they give rise to the formation of several pathotypes by the horizontal transfer of virulence genes, which can cause colibacillosis processes in more virulent calves, which is one of the most important causes of diarrhea in calves in the region of Cajamarca, compromising the sanitary viability in the herds.